2020
DOI: 10.1039/d0ra04950f
|View full text |Cite
|
Sign up to set email alerts
|

Water-based synthesis of photocrosslinked hyaluronic acid/polyvinyl alcohol membranes via electrospinning

Abstract: Homogeneous nanofibers and non-cytotoxic HA/PVA membranes were produced by conventional electrospinning method followed by photocrosslinking process, without using any organic solvent. The membranes showed great potential for biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…On the other hand, this increase in absorption might be related to the presence of a polar group in the crosslinker. In a previously published study, we showed that membranes had similar behavior in swelling tests, corroborating with this result . The results showed that the swelling behavior in the first 12 h for the 15 wt % MA membrane increased by 501%, while for 30 wt % MA, it increased by 296%.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…On the other hand, this increase in absorption might be related to the presence of a polar group in the crosslinker. In a previously published study, we showed that membranes had similar behavior in swelling tests, corroborating with this result . The results showed that the swelling behavior in the first 12 h for the 15 wt % MA membrane increased by 501%, while for 30 wt % MA, it increased by 296%.…”
Section: Resultssupporting
confidence: 89%
“…Finally, crosslinking was evidenced by the peak at 1700 cm –1 , which corresponds to the existence of the −COO– elongation, and by the change in the intensity at the peak of 1091 cm –1 , which is also related to the crosslinking between the −OH group of the structure of the PVA and the −CO grouping of the MA molecule, giving rise to the −COC– band. Still, another interesting observation was the disappearance of the peak at 1640 cm –1 , related to the −CC– bond of the MA molecule, suggesting its presence in the photocrosslinking reaction. , …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…[65] In addition, a method for manufacturing nanofiber dressings using a photo-crosslinking process without employing an organic solvent was also studied. [66] Table 3 presents recent approaches of composite materials used to improve the properties of dressings applied to hydrogels and nanofiber dressings based on PVA-HA.…”
Section: Type Composite Materials Materials Characteristicmentioning
confidence: 99%